2005
DOI: 10.1111/j.1524-4733.2005.00052.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Effectiveness of Lipid-Lowering Therapies in a Managed Care Environment

Abstract: While a dose-response relationship was observed, the effectiveness of statin therapy was less than stated in package labeling and only 72% of the users of the highest efficacy statins reached their ATP III goal. LLM use was inconsistent with that recommended by the NCEP ATP III CHD risk assessment. Hyperlipidemia treatment in the managed care setting remains in need of improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 27 publications
0
12
0
2
Order By: Relevance
“…26 Valuck et al and Meyer et al reported that patients treated with high-potency statin regimens were significantly more likely to attain an LDL-C goal < 100 mg per dL than patients treated with non-high-potency regimens. 17,27 In the present study, fewer patients with a new diagnosis of diabetes received lipid-modifying medication or attained the LDL-C goal of < 100 mg per dL than did newly diagnosed CHD patients. There are several reasons why this may have occurred.…”
Section: Nn Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…26 Valuck et al and Meyer et al reported that patients treated with high-potency statin regimens were significantly more likely to attain an LDL-C goal < 100 mg per dL than patients treated with non-high-potency regimens. 17,27 In the present study, fewer patients with a new diagnosis of diabetes received lipid-modifying medication or attained the LDL-C goal of < 100 mg per dL than did newly diagnosed CHD patients. There are several reasons why this may have occurred.…”
Section: Nn Discussionmentioning
confidence: 89%
“…Retrospective cohort studies have focused on patients with hyperlipidemia 15,26 and patients treated with lipid-modifying drugs, 27 or specifically with statins (during 1997-2004) [28][29][30][31] although there have been some retrospective cohort studies of high-risk patient groups (during 1996-2001). 16,17,32 Many of these studies focused on adherence to drug therapy. 28,29,31,32 Stacy and Egger reported that treatment with lipid-modifying drugs increased LDL-C goal attainment from 23% at baseline (prior to any drug treatment) to 68% over an average of 3.7 years later (in 2004).…”
Section: Nn Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with reports from earlier registries in Germany, for example the DUTY registry (2002) in 59,035 patients with DM (LDL-C target attainment rate < 100 mg/dl 16.6% at the end of observation) [19], the 4E registry (2001/2002) in the subgroup of 12,816 patients with DM in primary or secondary CHD prevention (LDL-C target attainment rates < 100 mg/dl 16% in men, 12% in women) [20], and the 2L cardio registry in high-risk or very-high-risk patients (37.1% < 100 mg/) [21]. No effectiveness data on the lipid management are available in the context of DMPs in Germany to date, but reports from the US in the managed care environment show that the situation is similarly suboptimal [22-24]. It must be noted that in the German DMPs for CHD the target value for LDL-C is set at 100 mg/dl, while in the DMPs for DM, lipid-lowering therapy is recommended, but no target value provided [4].…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous clinical trials, [32][33][34][35] statin therapy was categorized into three relative efficacy levels that were created based on expected amounts of LDL-cholesterol reduction from baseline: (a) low efficacy (≤ 30% LDL reduction): daily dose of fluvastatin ≤ 40mg, pravastatin ≤ 40mg, simvastatin ≤ 10mg, cerivastatin 0.2mg, or lovastatin ≤40 mg or 10mg twice daily, (b) moderate efficacy (31-40% LDL reduction): daily dose of fluvastatin 80mg, cerivastatin 0.3mg or 0.4mg, rosuvastatin ≤10mg, simvastatin 20mg or 40mg, atorvastatin 10mg, or (c) high efficacy (≥ 41% LDL reduction): simvastatin 80mg, atorvastatin ≥20mg, rosuvastatin ≥10mg, pravastatin 80mg, or lovastatin 80 mg).…”
Section: Lipid Lowering Pharmacotherapymentioning
confidence: 99%